Exploring the approximate number system in Sotos syndrome: insights from a dot comparison task. Issue 8 (7th February 2019) - Lane, C.; Van Herwegen, J.; Freeth, M.
Abstract: Background: Sotos syndrome is a congenital overgrowth condition associated with intellectual disability and an uneven cognitive profile. Previous research has established that individuals with Sotos syndrome have relatively poor mathematical ability, but domain‐specific numeracy skills have not been explored within this population. This study investigated the approximate number system (ANS) in Sotos syndrome. Method: A dot comparison task was administered to 20 participants with Sotos syndrome (mean age in years = 18.43, SD = 9.29). Performance was compared to a chronological agematched typically developing control group ( n  = 25) and a mental age‐matched Williams syndrome group ( n  = 24). Results: The Sotos group did not display an ANS deficit overall when compared to chronological agematched control participants. However, for trials where the size of the individual dots and the envelope area were negatively correlated with the total number of dots (incongruent trials), the Sotos group were less accurate than the typically developing group but more accurate than the Williams syndrome group, suggesting an inhibitory control deficit. Better accuracy on incongruent trials, but not congruent trials, was associated with higher quantitative reasoning ability for participants with Sotos syndrome. Conclusion: Overall, the findings suggest that ANS acuity is not impaired in Sotos syndrome but that numerical difficulties may be associated with an inhibitory control deficit for individuals with Sotos syndrome.